The use of Google Jamboard for synchronous collaborative reading strategies: The students’ acceptance - Khoiriyah Khoiriyah; Nurjalia Kairoty; Almathea Virdhausya Aljasysyarin (VELES Voices of English Language Education Society, 2022)
This study employed a mixed-method approach through administrating the Technology Acceptance Model (TAM) questionnaire and conducting in-depth interviews. TAM was used in this study to gain insight into the students' reactions to the technology used for online language learning, especially the acceptance of using Google Jamboard integrated with video conferencing for synchronous collaborative reading comprehension activities. Sixty-three undergraduate students were selected purposefully from the English Language Education Department who enrolled in Literal Reading course in a full-online learning instruction. From the findings, with the regard to the students' acceptance, they confirmed a positive attitude toward using this application, despite the fact that some of them thought it was a new application. As a result, perceived usefulness and the perceived ease of use were rated as moderately high. Many students agreed that the online platform used was immensely useful and simple to use. Meanwhile, some of them experienced technical issues when using this platform, impeding their learning process. Additionally, some pedagogical suggestions also further explored.